A note on convex functions - Yu-Ru Syau (International Journal of Mathematics and Mathematical Sciences)
In this paper, we give two weak conditions for a lower semi-continuous function on the n-dimensional Euclidean space Rn to be a convex function. We also present some results for convex functions, strictly convex functions, and quasi-convex functions.